1999
DOI: 10.1017/s0029665199000919
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and infectious diseases in the aged

Abstract: The incidence of infectious diseases, particularly respiratory diseases, increases with age. Age-associated decline in immune function contributes to the increased susceptibility of the aged to infections. Vitamin E supplementation has been shown to improve some aspects of immune function in aged animals and human subjects. The protective effect of vitamin E against viral or bacterial infections in experimentally-challenged young animals has been reported. We investigated the effects of supplementation with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 72 publications
0
13
0
2
Order By: Relevance
“…Vitamin E supplementation in old mice resulted in significantly lower viral titers on 2, 5, and 7 days postinfection, and a significant inverse correlation was observed between hepatic vitamin E levels and lung viral titers [107,121]. Han et al [108] showed that vitamin E supplementation of old mice infected with influenza significantly increased production of IL-2 and IFN-␥ but had no effect on IL-4 production.…”
Section: Mechanistic Studies For the Direct Effect Of Vitamin E On T mentioning
confidence: 99%
“…Vitamin E supplementation in old mice resulted in significantly lower viral titers on 2, 5, and 7 days postinfection, and a significant inverse correlation was observed between hepatic vitamin E levels and lung viral titers [107,121]. Han et al [108] showed that vitamin E supplementation of old mice infected with influenza significantly increased production of IL-2 and IFN-␥ but had no effect on IL-4 production.…”
Section: Mechanistic Studies For the Direct Effect Of Vitamin E On T mentioning
confidence: 99%
“…Clearly, the use of more effective vaccine strategies is needed and is likely to have a major impact on morbidity and mortality of respiratory tract infections in the elderly. Fuente et al, 1998;Enioutina et al, 2000;Moriguchi and Moruga, 2000), likely on the basis of antioxidant properties, and vitamin E has been shown to significantly reduce influenza virus titers in aged mice (Han and Meydani, 1999). Caloric restriction, a significant modulator of the aging process in laboratory animals, also appears to attenuate age-associated immunosenescence (Pahlavani and Richardson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is perhaps one of the most studied nutrients in relation to its immunoregulatory effect. Results from animal and human studies indicate that vitamin E deficiency impairs both humoral and cell‐mediated immune functions,1,2 while supplementation with vitamin E above the recommended levels has been shown to enhance immune response and to be associated with increased resistance against several pathogens 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Results from animal and human studies indicate that vitamin E deficiency impairs both humoral and cell-mediated immune functions, 1,2 while supplementation with vitamin E above the recommended levels has been shown to enhance immune response and to be associated with increased resistance against several pathogens. 3,4 A recommended dietary allowance (RDA) for vitamin E is currently set at 15 mg/ day of α-tocopherol for adults (ages above 19), 5 increased from the 10 mg recommended in the 10 th edition of the RDA book. 5 The average daily intake of vitamin E in the United States and other Western countries is estimated to be around 10 mg. Certain population groups, such as the elderly, are at greater risk for inadequate dietary intake of vitamin E. 6,7 Ryan et al 6 reported that more than 40% of elderly (65 to 98 years) persons had intakes of vitamin E that were below two-thirds the 1989 RDA.…”
Section: Introductionmentioning
confidence: 99%